Effect of Weed Management Practices on Productivity and Economics of Rice-Rice Crop sequence under Organic Production System - Srinivas, Manukonda; Anusha, B.; Reddy, C. Venkata; Satyanarayana, P. V.; Munirathnam, P. (International Journal of Bio-resource and Stress Management, 2019)
The present field investigation was carried out during kharif and rabi, 2017-18in deltaic alluvial soils of Regional Agricultural Research Station, Maruteru, Andhra Pradesh (534 122), India to evaluate the impact of different weed management practices on weed index and productivity of rice-rice cropping sequence under organic production system in Godavari delta region. The results revealed that incorporation of green leaf manure Sesbania sp. (3680 and 3587 kg ha-1) being at par with incorporation of locally available aquatic weed (Eichhornia sp.)+one manual hand weeding (3613 and 3407 kg ha-1), has significantly out yield all other treatments in terms of grain yield of rice-rice cropping system. Though, the practice of one mechanical weeding at 20-25 DAT+one manual hand weeding at 45-50 DAT has recorded lowest weed index values (1.0 and 0.3), the average grain yield was less by 323 kg ha-1 as compared to that of green leaf manure incorporation. The highest net returns (` 15250 and 14083 ha-1)and B:C ratio (1.50 and 1.46) were accrued with the practice of incorporation of green leaf manure (Sesbania) at 5 t ha-1. The incidence of leaf folder and brown plant hopper was below economic thresh hold level with the treatment incorporation of green leaf mulch (Sesbania sp.) and was closely followed by neem cake incorporation at 15 days before planting.